Electropharmacology of the bradycardic agents alinidine and zatebradine (UL-FS 49) in a conscious canine ventricular arrhythmia model of permanent coronary artery occlusion - Aidonidis, Isaac; Brachmann, Johannes; Rizos, Ioannis-Antonios; Zacharoulis, A.; Stavridis, I.; Toutouzas, P.; Kübler, Wolfgang (Cardiovascular drugs and therapy, 1995)
Myocardial infarction was produced in 27 anesthetized dogs by ligating the left anterior descending (LAD) coronary artery proximal to the septal branch. Nineteen of these animals survived the operation and were studied by programmed stimulation in a random sequence between the third and seventh days after the infarct. Complete electrophysiologic testing was implemented in each animal prior to and after single doses of either alinidine (1 mg/kg IV) or zatebradine (0.5 mg/kg IV). Alinidine prevented reinduction of sustained ventricular tachycardia (SVT) in only 2 of 9 dogs and zatebradine in 1 of 8 dogs. The SVT cycle length was not significantly changed in all cases in which it was still inducible despite drug administration (p>0.05). Alinidine lengthened the effective refractory period (ERP) in the AV node (p<0.01), whereas zatebradine did not induce a statistically significant prolongation. Conversely, zatebradine increased the left ventricular ERP, while alinidine left it almost unchanged. The rate-corrected QT interval (QTc) did not significantly differ from control values after the administration of either agents. Also, the duration and the ERP of infarctzone potentials, defined as late potentials, remained unaltered. The results indicate that the bradycardic agents alinidine and zatebradine do not exert antiarrhythmic efficacy against SVT induced during subacute myocardial infarction in conscious dogs. None of these drugs substantially changed ventricular electrophysiology or showed a drug-specific proarrhythmic effect.